Financial incentives and cognitive abilities: evidence from a forecasting task with varying cognitive load - Ondřej Rydval (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
I examine how financial incentives interact with intrinsic motivation and especially cognitive abilities in explaining heterogeneity in performance. Using a forecasting task with varying cognitive load, I show that the effectiveness of high-powered financial incentives as a stimulator of economic performance can be moderated by cognitive abilities in a causal fashion. Identifying the causality of cognitive abilities is a prerequisite for studying their interaction with financial and intrinsic incentives in a unifying framework, with implications for the design of efficient incentive schemes.
Keywords: C81; C91; D83; 330; Financial incentives; Cognitive ability; Heterogeneity; Performance; Experiment; Kognition; Leistungsmotivation; Leistungsanreiz; Ökonomischer Anreiz; Test